Anjou Vintage Bike (Anjou Vélo Vintage) - Sophie Lecomte; Océane Metais (Nicolaus Copernicus University in Toruń, 2018)
Purpose: To show that a local event can have an international reputation. Design / methodology / approach: We will see through the analysis of the routes, the organization of the event and the proposed animations how much Angers velo vintage can have at international and local level Research and practical limitations / implications: We will rely solely on published news articles and researches published.